Motion sickness in a fully automated vehicle: How does passenger feel when engaging in non-driving related activities - Karjanto, Juffrizal; Mohd Norzam, Muhammad Nur Aliff; Md. Yusof, Nidzamuddin; Mohd Jawi, Zulhaidi; Rauterberg, Matthias (School of Engineering, Taylor’s University, 2024)
Non-driving related activities (NDRA) such as reading and watching videos are some of the everyday activities to be done by the passenger when they are traveling in a vehicle. The passengers are expected to experience uncomfortable feelings such as motion sickness (MS) from mild MS and, worst case, vomit when engaging NDRA. Twenty-two participants (7 males and 15 females), aged between 20 and 28 years old (Mean = 23.05, SD = 2.51) that have Motion Sickness Susceptibility Questionnaire scores of more than 50% (Mean = 82.23, SD = 16.5) were selected to join the experiment using a within-subject design. This study focused on how the passengers felt when they engaged NDRA throughout the experiment session (before, during, and after the driven phase) when driving by a Defensive Automated Vehicle driving style. The results found that the participants experienced MS during and after the driven phase in both NDRAs. Also, the results found that reading activity induced more MS than watching a video.